Implementasi Sosial Media Marketing untuk Meningkatkan Citra Sekolah - Ira Nuriya Santi; Niken Nazira Kinsky (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
How well students perform at school is related to School Image. Incorporating a social media strategy is one way to improve a school's good image. Overall, social media is becoming increasingly important. Improving the school's image through social media marketing is the aim of this essay. This research study used a qualitative descriptive strategy, as detailed in scientific publications. The foundation of this approach is research methodology, which seeks to gather comprehensive and precise information about the problem at hand. Here, the author plays the role of researcher, planner, implementer, data collector, analyst, translator and reporter. From the research results it was found that there is social media to improve the image of the school. making social media an effective marketing and public relations method. There are three important elements in implementing social media: social media accounts, attractive visual content (photos, posters, infographics, videos), and narrative content (captions, news). The implementation of social media has been proven to improve the image of educational schools by facilitating the accessibility of information, showing achievements, superior activities and school activities, so that the public believes in the school's credibility.